Association between Minimum Dietary Diversity and Nutritional Status among Children Aged 6 to 24 Months in Terengganu - Zulkifli, Nur Arifah; Wee, Bee Suan (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
This cross-sectional study aimed to determine the association between food consumption quality, as determined by Minimum Dietary Diversity (MDD), and children’s nutritional status using anthropometric measurements. A total of 287 children (150 boys, 147 girls) aged 6 to 24 months from Kuala Nerus and Kuala Terengganu participated in this study through purposive sampling. Socio-demographics and food consumption of children were collected through interviews with the mother. Anthropometric comprised weight, height, while nutritional status was determined based on WHO Child Growth Standards. MDD was assessed using WHO Infant and Young Child Feeding (IYCF) Indicators Questionnaire. Children achieving the MDD were rated on four or more dietary variety scores, while those receiving less than four were categorized as